Recent Trends in RSV Immunoprophylaxis: Clinical Implications for the Infant - Acero-Bedoya, Santiago; Wozniak, Phillip S.; Sánchez, Pablo J.; Ramilo, Octavio; Mejias, Asuncion (American Journal of Perinatology, 2019)
Respiratory syncytial virus (RSV) remains the leading cause for hospitalizations in infants worldwide, resulting in significant health and financial burden. Since 1998, the humanized monoclonal antibody palivizumab remains the only available option licensed for the prevention of severe RSV disease in high-risk children, namely premature infants and those with chronic lung disease and congenital heart disease. In 2014, the American Academy of Pediatrics modified the recommendations on the use of RSV prophylaxis in these high-risk children, and limited its use to premature infants born at < 28 weeks' gestational age (wGA). Following this last guidance update, studies have confirmed that premature infants of 29 to 34 wGA remain at high risk for severe RSV disease, especially those of younger chronologic age. New and more cost-effective strategies are being developed that would help alleviate both the health and financial burden associated with severe RSV disease.
Keywords: respiratory syncytial virus; palivizumab; premature infants; disease severity; hospitalizations